The distribution of Dothistroma septosporum and its mating types in Poland. Issue 5 (12th January 2016) - Boroń, P.; Lenart‐Boroń, A.; Mullett, M.
Summary: Dothistroma needle blight (DNB), one of the most dangerous foliar diseases of pines, is the cause of much economic loss in pine plantations worldwide. The threat to pine‐dominated Polish forestry from this disease is therefore very large. However, the impact of DNB has not been high mainly due to the planting of P. sylvestris, a less susceptible native species. Until now, DNB was recorded in Poland only on highly susceptible exotic P . nigra . The current situation concerning the disease in Poland is described in this article. This disease, caused by Dothistroma septosporum, was first recorded in a single location (Domiarki) in southern Poland in 1990. This study reports the occurrence of D. septosporum in 37 new locations, demonstrating that the disease has now spread across the whole country. Pinus nigra remains the predominant host species in Poland. However, three new hosts for this fungus are reported, that is P. sylvestris, P. mugo and P. ponderosa . The ratio of D. septosporum mating types varies significantly between sites, ranging from an equal proportion of each mating type to single mating type populations. For the oldest known Polish population of D. septosporum, the mating type ratio has shifted towards equilibrium over time.